Women's economic empowerment : insights from Africa and South Asia - Grantham, Kate E.; Dowie, Gillian; Haan, Arjan de (Routledge studies in development and society, 2021)
"This book investigates the barriers to women's economic empowerment in the global south. Drawing on evidence from a wide range of countries, the book outlines important lessons and practical solutions for promoting gender equality. Despite global progress in closing gender gaps in education and health, women's economic empowerment has lagged behind, with little evidence that economic growth promotes gender equality. IDRC's Growth and Economic Opportunities for Women (GrOW) programme was set up to provide policy lessons, insights, and concrete solutions that could lead to advances in gender equality, particularly on the role of institutions and macroeconomic growth, barriers to labour market access for women, and the impact of women's care responsibilities. This book showcases rigorous and multi-disciplinary research emerging from this ground-breaking programme, covering topics such as school-to-work transition, child marriage, unpaid domestic work and childcare, labour market segregation, and the power of social and cultural norms that prevent women from fully participating in better paid sectors of the economy. With a range of rich case studies from Burkina Faso, Democratic Republic of the Congo, Ethiopia, Ghana, India, Kenya, Nepal, Rwanda, Sri Lanka, Tanzania, and Uganda, this book is perfect for students, researchers, practitioners, and policymakers working on women's economic empowerment and gender equality in the global south"--